Belize : Staff Report for the 2003 Article IV Consultation. (IMF Staff Country Reports; Country Report, 2004)
There is an urgent need to re-establish a viable external position through a comprehensive, swift, and sustained policy adjustment. The fiscal adjustment will need to rest on both wide-ranging tax revenue measures and substantial expenditure restraint, including a freeze of current expenditure. Executive Directors welcome the government's decision to restructure the Development Finance Corporation. Existing import restrictions should be eliminated or converted into tariffs to improve resource allocation, increase revenue, and reduce administrative costs. Belize statistical information is inadequate to monitor macroeconomic developments sufficiently.